1999
DOI: 10.1007/s11325-999-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Breathing at High Altitude

Abstract: Sleep at high altitude is characterized by poor subjective quality, increased awakenings, frequent brief arousals, marked nocturnal hypoxemia, and periodic breathing. A change in sleep architecture with an increase in light sleep and decreasing slow-wave and REM sleep have been demonstrated. Periodic breathing with central apnea is almost universally seen amongst sojourners to high altitude, although it is far less common in long-standing high altitude dwellers. Hypobaric hypoxia in concert with periodic breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 58 publications
(125 reference statements)
5
39
0
Order By: Relevance
“…[17][18][19][20] In our research, we concentrated on the breathing abnormalities occurring in patients exposed to high altitude. The following variables CAL, VL, and CD were short in duration.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] In our research, we concentrated on the breathing abnormalities occurring in patients exposed to high altitude. The following variables CAL, VL, and CD were short in duration.…”
Section: Discussionmentioning
confidence: 99%
“…91,99 It is important to note that this occurs despite the fact that hypocapnia increases over time. As such, it appears that the responsiveness of the ventilatory inhibition by hypocapnia is improved with acclimatization to altitude.…”
Section: Effects Of Acute Altitude Residence On Sleep Qualitymentioning
confidence: 99%
“…While this periodicity decreases with successive nights at altitude, it has been shown to persist at elevations above 4500m. 91 Early studies on sleep physiology at altitude showed the alteration of sleep cycles experienced by subjects. Joern et al (1970) found that at pressures similar to moderate altitudes, sleep stage distribution was altered so that Stages 3 and 4 were almost eliminated and REM sleep was reduced by 50%.…”
Section: Effects Of Acute Altitude Residence On Sleep Qualitymentioning
confidence: 99%
“…Subsequent studies have shown similar results. 91,[93][94][95] Although it appears that the increased arousals during sleep at altitude are connected to periodic breathing, the mechanisms that contribute to the shift in sleep patterns are poorly understood. 90 The mechanism of periodic breathing, though, was first demonstrated by Douglas and Haldane (1909).…”
Section: Effects Of Acute Altitude Residence On Sleep Qualitymentioning
confidence: 99%